Tolerance of Rhizobium Isolates to Certain Heavy Metals - Esra Hussien; Raad Sultan; Vineetha Edavana (College of Education for Pure Sciences, 2024)
In this study, five isolates of Rhizobium bacteria were isolated from root nodules of different leguminous plants as follows: Ensifer meliloti EW7 from Medicago sativa L., Ensifer fredii bv. fredii EW33 from Vigna unguiculata L., R. leguminosarum bv. phaseoli EW15 from Phaseolus vulgaris L., R. leguminosarium bv. trifolii EW19 from Trifolium alexandrium L. and R. legumiosarium bv. viciae EW30 from viciae faba L., which were collected from different cultural areas in Nineveh, Governorate-Iraq. Then pure Rhizobium colonies were obtained, and their agronomic and biochemical characteristics were studied. These isolates were a rod-shaped and negative Gram-stain. Whereas positive for TSI, BTB, CUT, Kovak’s test, urase test, and for the methyl red and Voges-Proskauer tests. All of the rhizobial isolates showed positive results for the catalase test and for motility when tested on TY semi-solid medium. Tolerance of local Rhizobium isolates was tested against four heavy metal salts as follows: Pb(CH3COO)2, Nicl2, CdCl2, and CoCl2. The isolates showed a varied response to tolerance or resistance to heavy metal salts. The highest mean of inhibition zone reached 21mm in isolate Ensifer fredii bv. fredii EW33 against heavy metal CdCl2. Whereas the isolate R. legumiosarium bv. viciae, EW30 showed less affects which mean of inhibition zone was 9 mm only with 5000 concentration of heavy metal CoCl2.